Chemerin as a Biomarker for Periodontitis in Systemically Healthy and Type 2 Diabetic Patients (Mustansiria Dental Journal, 2022)
Aim of the study: The aim of the study was to evaluate the salivary levels of chemerin in patients with periodontitis and type 2 diabetes mellitus.Materials and methods: A total of 88 subjects were divided into four groups; 13 systemically healthy individuals having a healthy periodontium (control group), 25 patients with type 2 diabetes mellitus and healthy periodontium (T2DM group), 25 patients with generalized periodontitis (P group), 25 patients with generalized periodontitis and type 2 diabetes mellitus (P-T2DM group). The clinical periodontal parameters including plaque index (PLI), bleeding on probing (BOP), probing pocket depth (PPD), and clinical attachment loss (CAL) were determined. Unstimulated saliva was gathered, and the concentration of chemerin was estimated utilizing an enzyme-linked immunosorbent assay.Results: The results showed that the mean concentrations of chemerin were highest in the P-T2DM group with a mean (of 1.598±0.1499 ng/ml) followed by the P group (1.445±0.1021 ng/ml), T2DM group (1.368±0.096 ng/ml), and control group (1.229±0.152 ng/ml), respectively. There was a statistically significant difference among groups at (p